Mitigating chromium toxicity and enhancing rice productivity in chromium-affected regions of Odisha, India - Dibakar Ghosh; Sayed Islam; Madhumita Das; K. Laxminarayana; Ashis Maity; Ankita Jha; Partha Debroy; S. K. Jena; Arjamadutta Sarangi (Paddy and Water Environment, 2026)

Appraising aquifer storage recovery (ASR) for irrigation potential in a coastal environment - Md.Helal Ahmmed; Md.Sabbir Hossain; Sara Nowreen; Md. Moniruzzaman; A.H.M. Shofiul Islam Molla Jamal; Mohammad Moniruzzaman; Iffat Jahan Shammee; Ratan Kumar Majumder; Afroza Sharmin; Shahrina Akhtar; Nabanita Chowdhury; Saifullah Sayed (Journal of Hydrology, 2026)

Mitigating surface industrial heat island effects in arid environments: A machine learning approach to sustainable planning - Islam M. Hamdi; Eman Albalawi; Elsayed K. AbdAlmapoed; Sayed R. AbdElaal (Energy and Buildings, 2026)

Olive (Olea europaea) phenolics for the control of psoriasis via targeting SMYD2 and IL-17A protein–protein interaction networks - Md Ashiq Mahmud; Mohamed M. Mohyeldin; Md Towhidul Islam Tarun; Abu Bakar Siddique; Sitanshu S. Singh; Khalid A. El Sayed (Journal of Natural Medicines, 2026)

Assessment of groundwater quality and human health risks using deterministic and probabilistic approaches in Chandina Upazila, Cumilla, Bangladesh - Md. Tahsinur Rahman; Mohammad Ismail; Sajib Ahmed; Sayed Abu Johany; Ajoy Deb Nath; Kanai Lal Das; Md Mozammel Haque; Mohammad Saiful Islam Bhuiyan (Environmental Geochemistry and Health, 2026)

First report of Alternaria arborescens causing leaf spot on quinoa (Chenopodium quinoa) in Bangladesh - Bilkis Nahar; Bodrun Nessa Shompa; Sakib Srower Santo; Al Mahmud Shoaib; M. Salahuddin M. Chowdhury; Jamilur Rahman; F. M. Aminuzzaman; Md. Nazrul Islam; Md. Iyasir Arafat; Sayed Mohammad Mohsin (Australasian Plant Pathology, 2026)

Revisiting trace metal pollution, sources, and risks in road dust from Dhaka megacity, Bangladesh - Md. Eusuf Sarker; Sumaya Nasrin; Mir Md. Mozammal Hoque; Md Sariful Islam; Yeasmin Nahar Jolly; Shirin Akhter; Abu Sayed Md. Faysal; Mehedi Hasan Jony; Nafis Wadud; Tanmoy Roy Tusher (Air Quality, Atmosphere & Health, 2026)

Assessment of heavy metal contamination and associated risks in fish feed and pond-cultured fish - Tafsir Hasan; Md Tasif Amir Sufal; Sha Md Shahan Shahriar; Md Sarwar Hossain; Md Shohanur Rahman; Md Mahfujul Hasan; Sumaiya Dipti; Md Saiful Islam; Md Khairul Islam; Sayed M.A. Salam (Food Control, 2026)

Guava leaf (Psidium guajava) byproducts in animal and fish diets: a review of health benefits, immunomodulation, and sustainable applications - Khaled M. Al-Marakby; Islam G. Abdelghani; Ehab El-Haroun; Zeinab Mahasneh; Roshmon Thomas Mathew; Asmaa M. Sheiha; Mohamed F. Abo El-Maati; El-Sayed Hemdan Eissa; Md Altafur Rahman; Sameh A. Abdelnour (Tropical Animal Health and Production, 2026)

Improving growth traits in rabbits: a comparative study of Gabali, New Zealand White, and their hybrids using 18S rDNA sequencing - Hairul Islam Mohamed Ibrahim; Abdullah Sheikh; Roshmon Thomas Mathew; Muhammad Munir; Gamal Bekhet; El-Sayed Hemdan Eissa; Sameh A. Abdelnour; Mohamed D. Mahran (Tropical Animal Health and Production, 2026)

Oil sludge from an environmentally hazardous pollutant to an efficient source for energy production via thermal/ catalytic pyrolysis routes - Mohamed N.A. Mahmoud; Esraa M. El-Fawal; Ahmed M.A. El Naggar; Asmaa I. Zahran; Hussien A. El Sayed; Islam M. El-Sewify; Bassem H. Heakal; Mostafa M.H. Khalil (Fuel, 2026)

Assessment of urban heat island effects in industrial areas of Egypt using robust statistical methods - Islam Hamdi; Elsayed K. AbdAlmapoed; Sayed R. AbdElaal (Remote Sensing Applications: Society and Environment, 2025)

Biosynthesis of bicyclo[3.3.1]nonane derivatives in Hypericum sampsonii - Lukas Ernst; Hui Lyu; Pi Liu; Christian Paetz; Hesham MB Sayed; Tomke Meents; Hongwu Ma; Ludger Beerhues; Islam El-Awaad; Benye Liu (Phytochemistry Letters, 2025)

Butylated hydroxytoluene (BHT) improved semen quality and sperm DNA of frozen-thawed Arabian stallions preserved in modified INRA-82 extender - Amal M. Aboelmaaty; Islam El-Sayed El-Seadawy; Mohamed Saeed Kotp; Alaa A. Mohamed; Hazem Ahmed El-Debaky; Diya A. El-Badry; Abeer M. Anwer; Tsvetan Tsvetkov; Teodora Daneva; Mahmoud A. Elgabry (Journal of Equine Veterinary Science, 2025)

Exploring the properties of Rhizobium sp. HR1101-4 exopolysaccharide: introducing a novel exopolysaccharide in food industry - Umma Ayman Tishun; Farzana Sayed Sraboni; Mst. Mamotaz Mohal; Md. Rahat Manik; Shoriful Islam Joy; Asad Syed; Ling Shing Wong; Shirmin Islam; Md. Abu Saleh; Shahriar Zaman (Biotechnology Letters, 2025)

Numerical Breakdown of Contemporary Banana Production and Its Prospects in Bangladesh - Sayed Mohibul Hossen; Rakibul Islam (Applied Fruit Science, 2025)

Investigating the effects of granite, marble, granodiorite, and ceramic waste powders on the physical, mechanical, and radiation shielding performance of sustainable concrete - Alaa A. Mahmoud; Alaa A. El-Sayed; Ayman M. Aboraya; Islam N. Fathy; Mohamed A. Abouelnour; Bassam A. Tayeh; Islam M. Nabil (Annals of Nuclear Energy, 2025)

Acetamiprid-induced pulmonary toxicity via oxidative stress, epithelial-mesenchymal transition, apoptosis, and extracellular matrix accumulation in human lung epithelial cells and fibroblasts: Protective role of heat-killed Lactobacilli - Samah S. Arafa; Heba A. Elnoury; Sahar Badr El-Din; Mohamed A. Sakr; Fatma Fawzi Hendawi; Rehab Ali Elsayed Masoud; Samia Soliman Barghash; Doaa Sabry Elbehairy; Ayat Abdelaty Hemeda; Islam Mostafa Farrag; Doaa Sayed Abdelrahman; Amira Mohammad Elsadek; et al. (Food and Chemical Toxicology, 2025)

Impact of ingested microplastics on phenotypic traits and biochemical parameters in Nile tilapia (Oreochromis niloticus) juvenile - Sheikh Mustafizur Rahman; Fatima Tuz Zohora; Tania Sultana Mohona; Momotaz Khanom; Md. Moshiur Rahman; Md. Golam Sarower; Muhammad Abdur Rouf; Md. Nazrul Islam; Roshmon Thomas Mathew; Yousef Ahmed Alkhamis; Yousof Naser Alrashada; Lamya Ahmed Alkeridis; et al. (Aquaculture International, 2025)

Combined Effect of Leaching Process and Biochar Application on the Restoration of a Coastal Mild Saline-alkali Soil and the Growth of Pak Choi (Brassica chinensis L.) - Yiqun Gong; Yitong Dan; Huan Wang; Wenxin Gao; Jing Miao; Wenjing Sang; Hui Yuan; Zheng Shen; Mohamed E. A. El-sayed; Islam A. Abdelhafeez; Yalei Zhang (Water, Air, & Soil Pollution, 2024)

Biodegradation and antimicrobial capability-induced heavy metal resistance of the marine-derived actinomycetes Nocardia harenae JJB5 and Amycolatopsis marina JJB11 - Mohamed H. El-Sayed; Muaz M. Abdellatif; Howayada M. Mostafa; Islam A. Elsehemy; Abd El-Nasser A. Kobisi (World Journal of Microbiology and Biotechnology, 2024)

Co-impacts of cation type and humic acid on migration of polystyrene microplastics in saturated porous media - Wenxin Gao; Xiaoxia Wang; Yinzhu Diao; Yiqun Gong; Jing Miao; Wenjing Sang; Hui Yuan; Zheng Shen; Mohamed E.A. El-sayed; Islam A. Abdelhafeez (Journal of Environmental Management, 2024)

Novel Probiotic Lactic Acid Bacteria with In Vitro Bioremediation Potential of Toxic Lead and Cadmium - Md. Sayed Hasan; Md. Zakirul Islam; Ruckshana Islam Liza; Md. Abid Hasan Sarker; Mohammad Ashiqul Islam; Md. Harun-ur-Rashid (Current Microbiology, 2022)

The diagnostic accuracy of intraoperative frozen section biopsy for diagnosis of sentinel lymph node metastasis in breast cancer patients: a meta-analysis - Alaa Ahmed Elshanbary; Alaa Abdelsameia Awad; Alaa Abdelsalam; Islam H. Ibrahim; Walid Abdel-Aziz; Youssef Bahaaeldin Darwish; Alaa Saad Isa; Boutheyna Drid; Marwa Gamal Mustafa; Radwa Hamdy Allam; Amira A. Abo Ali; Anas Zakarya Nourelden; et al. (Environmental Science and Pollution Research, 2022)
Sentinel lymph node (SLN) sampling is important for evaluating the nodal stage of breast cancer when the axillary nodes are clinically free of metastasis. The intraoperative frozen section (IFS) of SLN is used for lymph node assessment. This meta-analysis aims to provide evidence about the diagnostic accuracy and the applicability of IFS of SLN in breast cancer patients. Data were collected by searching PubMed, Cochrane, Scopus, and Web of Science electronic databases for trials matching our eligibility criteria. The statistical analysis included the sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, and pooled studies’ diagnostic odds ratio outcomes. The analyses were conducted using the Open Meta-analyst software. This meta-analysis pooled the results of 110 studies. The overall sensitivity of IFS for SLN metastasis was 74.7%; 95% CI [72.0, 77.2], P < 0.001. It was 31.4% 95% CI [25.2, 38.3], P < 0.001 for the micro-metastasis, and 90.2%; 95% CI [86.5, 93.0], P < 0.001 for the macro-metastasis. The overall specificity was 99.4%; 95% CI [99.2, 99.6], P < 0.001. The overall positive likelihood ratio was 121.4; 95% CI [87.9, 167.6], P < 0.001, and the overall negative likelihood ratio was 0.226; 95% CI [0.186, 0.274], P < 0.001. The overall diagnostic odds ratio of IFS for diagnosing SLN metastasis was 569.5; 95% CI [404.2, 802.4], P < 0.001. The intraoperative frozen section of SLN has good sensitivity for diagnosing breast cancer macro-metastasis. However, the sensitivity is low for micro-metastasis. The specificity is very satisfactory.

Optimizing hyperparameters of deep hybrid learning for rainfall prediction: a case study of a Mediterranean basin - Ahmed Elbeltagi; Bilel Zerouali; Nadjem Bailek; Kada Bouchouicha; Chaitanya Pande; Celso Augusto Guimarães Santos; Abueza Reza Md. Towfiqul Islam; Nadhir Al-Ansari; El-Sayed M. El-kenawy (Arabian Journal of Geosciences, 2022)

“Anosmia” the mysterious collateral damage of COVID-19 - Abdulrahman K. Ahmed; Reem Sayad; Islam A. Mahmoud; Aya M. Abd EL-Monem; Salma H. Badry; Islam H. Ibrahim; Mahmoud HR Hafez; Mohamed A. El-Mokhtar; Ibrahim M. Sayed (Journal of NeuroVirology, 2022)

Seasonal dynamics of phytoplankton community and functional groups in a tropical river - Md. Ayenuddin Haque; Md. Abu Sayed Jewel; Most. Mahmuda Akhi; Usman Atique; Alok Kumar Paul; Sonia Iqbal; M. Shahanul Islam; Simon Kumar Das; M. Manjurul Alam (Environmental Monitoring and Assessment, 2021)

Assessment of Heavy Metal Concentration in Water, Sediment and Common Fish Species of Dhaleshwari River in Bangladesh and their Health Implications - Evena Parvin Lipy; Mahmuda Hakim; Liton Chandra Mohanta; Dipa Islam; Chadni Lyzu; Dipankar Chandra Roy; Iffat Jahan; Samina Akhter; Mohammad Raknuzzaman; Md. Abu Sayed (Biological Trace Element Research, 2021)

Multivariate approaches to determine the relationship between fish assemblage structure and environmental variables in Karatoya River, Bangladesh - Most. Mahmuda Akhi; Md. Abu Sayed Jewel; Md. Ayenuddin Haque; Biplob Kumer Sarker; Mst. Samsad Khatun; Alok Kumar Paul; M. Shahanul Islam; Simon Kumar Das (Community Ecology, 2020)

Effects of Silver Nanoparticles on Burn Wound Healing in a Mouse Model - Lamiaa G. Wasef; Hazem M. Shaheen; Yasser S. El-Sayed; Thanaa I. A. Shalaby; Dalia H. Samak; Mohamed E. Abd El-Hack; Abdullah Al-Owaimer; Islam M. Saadeldin; Amany El-mleeh; Hani Ba-Awadh; Ayman A. Swelum (Biological Trace Element Research, 2020)

Efficient photocatalytic removal of safarnin-O dye pollutants from water under sunlight using synthetic bentonite/polyaniline@Ni2O3 photocatalyst of enhanced properties - Mostafa R. Abukhadra; Mohamed Shaban; Fatma Sayed; Islam Saad (Environmental Science and Pollution Research, 2018)

Screening of rice landraces (Oryza sativa L.) for seedling stage salinity tolerance using morpho-physiological and molecular markers - Md. Tahjib-Ul-Arif; M. Abu Sayed; Mirza Mofazzal Islam; M. Nurealam Siddiqui; S. N. Begum; M. Afzal Hossain (Acta Physiologiae Plantarum, 2018)

Selectivity Improvement for Spectrofluorimetric Determination of Oseltamivir Phosphate in Human Plasma and in the Presence of Its Degradation Product - Mahmoud A. Omar; Sayed M. Derayea; Islam M. Mostafa (Journal of Fluorescence, 2017)